KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI DAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 8 PADANG - Yeni, Irma; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is three. First, it describes the skills of reading comprehension text description grade VII SMP Negeri 8 field. Second, it describes the writing skills text description grade VII SMP Negeri 8 field. Third, describing the correlation of the reading comprehension text descriptions and writing skills text description grade VII SMP Negeri 8 field. This research type is quantitative descriptive method. The design used in this research is the design correlation. This research population is grade VII SMP 8 Negeri Padang are registered on the 12th school year 2018/2019, i.e. as many as 255 students. The sample in this research are determined by proportional random sampling of 15% of the population, i.e. 40 students. The data obtained through two types of tests i.e. objective tests to measure the skills of reading comprehension text description and performance tests to measure the skills of writing a text description. The results of the research there are three. First, the skills of reading comprehension text description grade VII SMP Negeri Padang 8 are on good qualifications (B) by the value of the average 79.17. Second, the skills of writing text descriptions grade VII SMP Negeri Padang 8 are on good qualifications (B) with an average of 81.25. Third, there is a significant correlation between reading skills of calss VII students of SMP Negeri 8 Padang in the freedom degree and 95% significant level. H0 is rejected an H1 is accepted because the test results prove that the count is greater than ttable, namely 7,56>2,68.Â Kata kunci: Korelasi, Keterampilan, Membaca Pemahaman, Menulis